Achegas ao exame do crecemento da acumulación industrial arxentina na posconvertibilidade (2005-2011) e a súa comparación coa fase de incremento neoliberal (1993-1998) - Naspleda, Federico Daniel (Revista galega de economía.)
Several discussions have taken place in relation to the Argentine industrial accumulation from the neoliberal stage (also known as "convertibility") until its breakup in the post-convertibility stage. The discussions are organized around whether significant structural changes in the predominant industrial profile were manifested between both periods -according to the prevalence in the manufacturing of industrial commodities-, or if there are more continuities. In the present study, the mentioned debates contribute by examining the industry, on the one hand, under the dynamics of the accumulation of the sectors that integrate it, and on the other, according to an input-output model. In turn, in order to study the characteristics of manufacturing growth in post-convertibility and establish comparisons with convertibility, the phases of cumulative increase of the crisis and recovery phases are differentiated. This study contributes from this approach to the theses that sustain the persistent continuities in both stages.